PERAN FAKTOR PELATIHAN SUMBER DAYA MANUSIA TERHADAP PENGELOLAAN SISTEM INFORMASI AKADEMIK PADA SEKOLAH K DI KOTA MALANG - Olivia Cahyo Saputri (Jurnal Manajerial, 2017)
Education is one thing which is very important for the young people. A system of academic information should really be taken care of for the success of an institution of education. The research conducted at the K School using the method of approach descriptive kualitatif to analyze the problem and found the settlement of problems there. In the study of K School, the methode of solving this problem using methods of training that can be used to solve problems for K School to efficiency and improve their education, and do more evaluation for their good performance academic information